Human monoclonal antibody fragments that neutralize bio-functions of surface exposed proteins of type a influenza viruses - Tippawan Pissawong (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The surface proteins of the influenza A virus, namely hemagglutinin (HA), neuraminidase (NA), and matrix protein-2 (M2) are surface exposed and thus are vulnerable targets for neutralizing antibodies. HA is the most abundant protein on the viral surface and the virus uses this protein as a ligand for host cell receptor binding and subsequent cellular entry by receptor mediated endocytosis. In the acidic endosome, a conformational change in the cleavage-active HA molecule induces fusion of the HA to the host endosomal membrane, allowing the exit of the viral RNPs into the host cytoplasm and subsequent nuclear import for replication. NA is a sialidase enzyme that cleaves the NeuAcα2,3Gal or NeuAcα2,6Gal on new virions and releases them from the infected cell. The M2 protein forms a homotetramer which is a highly selective channel for H+ influx into the intra-endosomal virion causing a dissociation of matrix protein-1 (M1) from the viral RNPs, allowing entry of the latter into the host cytosol. In the late stage of viral replication, M2 prevents acid-induced conformational change of newly synthesized hemagglutinin molecules that are cleaved in the trans-Golgi network. M2 functions also in inhibition of autophagy in infected cells causing accumulation of autophagosomes (macroautophagosome) to help the survival of the influenza virus in the infected cell. In addition, HA, NA, and M2 proteins also work together in viral assembly and budding. HA and NA help the M2 amphipathic helix in causing membrane curvature at the neck of the budding virion leading to membrane scission and virus release. As such, antibodies that interfere with HA, NA, and M2 functions have high potential as sole or adjunct therapeutic agents for influenza. In this study, fully human monoclonal single chain antibody variable fragments (HuScFv) specific to HA, NA, and M2 of the influenza A virus were generated by using phage display technology. Influenza viruses adsorbed on the human erythrocyte ghosts were used as a phage biopanning antigen for selecting phage clones that dispalyed HuScFv from a human ScFv phage display library. The HuScFv specific to HA, NA and/or M2 derived from huscfv-phagemid transformed E. coli clones can be classified into 4 groups: HuScFv that bound to HA, NA, and M2 (clones no. 2, 10, 26, and 54); HuScFv that bound to HA and NA (clone no. 53); HuScFv that bound to M2 (clones no. 15 and 51); and HuScFv that bound to HA (clone no. 99). HuScFv from four selected clones which had different antigenic specificities and amino acid sequences particularly at their complementarity determining regions (CDRs), i.e., clones no. 26, 51, 53, and 99, were tested for their efficacies in interfering with the influenza virus replication cycle in mammalian cell cultures. The results of the plaque assay revealed that the HuScFv of all clones could reduce the numbers of influenza virus foci in the HuScFv treated-infected cells. Phage clones displaying HuScFv that bound specifically to full length recombinant M2 (rM2) were also selected from the human ScFv phage display library. Four huscfv-phagemid transformed E. coli clones, i.e., no. 2, 19, 23 and 27, expressed HuScFv that bound not only to the rM2 but also to native M2 (nM2) in influenza virus infected cell homogenates and inside the cells. The HuScFv2, 19, 23, and 27 which had different amino acid sequences in immunoglobulin frameworks and CDRs could similarly reduce the amounts of viruses both in the culture supernatants and inside the cells infected with adamantane sensitive and resistant A/H5N1 strains belonging to different clades. A phage mimotope (peptide) search and multiple alignments revealed that conformational epitopes of HuScFv2 located at the residues important for ion channel activity, anti-autophagy, and M1 binding. Epitopic residues of HuScFv19 located at the M2 amphipathic helix and cytoplasmic tail important for anti-autophagy, virus assembly, morphogenesis, and release. The epitope of HuScFv23 involved residues important for the M2 activities similar to HuScFv2 and also amphipathic helix residues for viral budding and release. For the HuScFv27 epitope, it spanned ectodomain, ion channel, and anti-autophagy residues. The results of computerized homology modeling and molecular docking conformed to the epitope identification by phages. M2 epitopes bound by HuScFv2, 19, 23, and 27 are conserved across influenza A subtypes and human pathogenic clades of H5N1, indicating that the HuScFv have anti-influenza A activity. Although molecular mechanisms of the HA-, NA-, and/or M2-specific-HuScFv(s) in interfering with the influenza virus replication cycle await experimental validations, these small antibody fragments which are fully human proteins have high potential for developing further as safe, novel, and mutation tolerable anti-influenza agents, especially against drug resistant variants.